1988
DOI: 10.1002/aic.690340416
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of chlorination of alumina using supercritical CCl4

Abstract: In the Alcoa smelting process, anhydrous aluminum chloride is electrolytically converted to aluminum metal. This process could have a major impact on the aluminum industry if an efficient way of making the anhydrous aluminum chloride from alumina were found (Othmer et al., 1978). To make aluminum chloride, carbon and chlorine must be added to alumina. The carbon and chlorine reactants can take many forms, but carbon tetrachloride is convenient in that the carbon and chlorine are together in a single molecule. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These results showed that the catalyzed reaction could occur at temperatures lower than those used previously provided the pressure was sufficiently high. Herrick et al (1988) reacted solid alumina with CCI, at conditions that exceeded the critical point of the carbon tetrachloride. They examined this heterogeneous reaction, because it provides a potential route to AICl,, which can be electrolytically converted to aluminum metal.…”
Section: \ mentioning
confidence: 99%
“…These results showed that the catalyzed reaction could occur at temperatures lower than those used previously provided the pressure was sufficiently high. Herrick et al (1988) reacted solid alumina with CCI, at conditions that exceeded the critical point of the carbon tetrachloride. They examined this heterogeneous reaction, because it provides a potential route to AICl,, which can be electrolytically converted to aluminum metal.…”
Section: \ mentioning
confidence: 99%